2023
DOI: 10.3390/ijms24044160
|View full text |Cite
|
Sign up to set email alerts
|

The State of the Organs of the Female Reproductive System after a 5-Day “Dry” Immersion

Abstract: The impact of weightlessness on the female reproductive system remains poorly understood, although deep space exploration is impossible without the development of effective measures to protect women’s health. The purpose of this work was to study the effect of a 5-day “dry” immersion on the state of the reproductive system of female subjects. On the fourth day of the menstrual cycle after immersion, we observed an increase in inhibin B of 35% (p < 0.05) and a decrease in luteinizing hormone of 12% (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…This raises a question of cardiovascular risk for long-term missions. Of note, while sharp decreases in plasma progesterone concentration were reported after 5 days of DI compared to ambulatory conditions on the same day of the cycle in healthy females 73 , menstrual cycle was not controlled in our female participants. Although this limitation needs to be acknowledged, we did not observe differential metabolic responses to DI between individuals with high versus low plasma progesterone and estradiol levels, suggesting that the effects of DI may be stronger than hormonal modifications.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This raises a question of cardiovascular risk for long-term missions. Of note, while sharp decreases in plasma progesterone concentration were reported after 5 days of DI compared to ambulatory conditions on the same day of the cycle in healthy females 73 , menstrual cycle was not controlled in our female participants. Although this limitation needs to be acknowledged, we did not observe differential metabolic responses to DI between individuals with high versus low plasma progesterone and estradiol levels, suggesting that the effects of DI may be stronger than hormonal modifications.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, the question of the effect of DI on the cycle and more generally on reproductive system was not explored in our study. Interestingly, the very recent data on the effect of 5-day dry immersion on the female reproductive system 73 show a sharp decrease in progesterone after immersion.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It was shown that after being in "dry" immersion, the content of anti-Mullerian hormone does not change, but inhibin B increases, which is produced by granulosa cells and can be a marker of an increase in their number. Moreover, the size of the antral follicles and the dominant follicle increases, which can be considered a positive criterion for a maturing oocyte [5], which requires direct experimental confirmation.…”
Section: Introductionmentioning
confidence: 99%